The Metaphor of War in Political Discourse on COVID-19 in Uganda - Atuhura, Dorothy (Frontiers in Communication, 2022)
The article examines the use of the metaphor of war in political communication on the novel COVID-19 pandemic in Uganda using two analytical tools of the social representation theory, anchoring and objectification. Drawing data for analysis from six widely televised presidential addresses to the nation on COVID-19 made by Uganda’s president, H.E. Yoweri Kaguta Museveni during the months of March 2020 to September 2020, the article argues that during the time of the COVID-19 pandemic, there was a persistent dominant use of the metaphor of war by government representatives as a rhetorical device to communicate about and to make intelligible an emerging unknown virus as a threat that should be managed through combat behavior. In so doing, the use of the war metaphor and its implied call for combat behavior to control, manage, and eradicate the virus spread engendered consequences such as standardizing hegemonic understanding of the nature and causes of the virus as well as normalizing and legitimizing interventions that the government adopted to manage it.